PERBANDINGAN MANAJEMEN SEKTOR PEMERINTAH DENGAN SEKTOR SWASTA - Zuhrizal Fadhly (Jurnal Public Policy, 2016)
Public sector service management model has some characteristics that are different from the private sector. The private sector is based on the choice of the individual in the market. Organizations in the private sector are required to be able to meet the tastes and individual selection decisions to meet each individual customer. Such a state is different from what happened in the public sector. The public sector is not based on individual choice in the market but a collective choice in government. Public sector organizations based on the demands of society is collective. Keywords: Comparative Management With the Government Sector Private Sector